2009
DOI: 10.1590/s0066-782x2009000800011
|View full text |Cite
|
Sign up to set email alerts
|

Preditores de mortalidade hospitalar em pacientes com embolia pulmonar estáveis hemodinamicamente

Abstract: In hemodynamically stable patients with pulmonary embolism, age > 65 years, bed rest > 72h, chronic cor pulmonale, sinus tachycardia and tachypnea were independent predictors of in-hospital mortality. However, further validation of the prediction model in other populations is required so that it can be incorporated into the clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
2
7
0
1
Order By: Relevance
“…In total, among the 71 studies, 64 were found to be including variables specific to the domain of PE and its prognosis: 17 were identified as model construction studies, 65 67–69 85 87 89 90 92 110 118 121–124 129 135 41 as model external validation or model update studies 70 72 74–78 80–84 86 88 91 93–97 99 101 102 104 106–109 111–117 119 120 127 130 131 134 and 6 as measuring model impact. 66 71 100 128 132 133 For the remaining seven studies, variables in the model were either originally not specific to PE 98 103 105 or to its prognosis 73 or concerned a hospital checklist 79 125 126 that is a combination of prognostic and practical variables for outpatient management.…”
Section: Resultsmentioning
confidence: 99%
“…In total, among the 71 studies, 64 were found to be including variables specific to the domain of PE and its prognosis: 17 were identified as model construction studies, 65 67–69 85 87 89 90 92 110 118 121–124 129 135 41 as model external validation or model update studies 70 72 74–78 80–84 86 88 91 93–97 99 101 102 104 106–109 111–117 119 120 127 130 131 134 and 6 as measuring model impact. 66 71 100 128 132 133 For the remaining seven studies, variables in the model were either originally not specific to PE 98 103 105 or to its prognosis 73 or concerned a hospital checklist 79 125 126 that is a combination of prognostic and practical variables for outpatient management.…”
Section: Resultsmentioning
confidence: 99%
“…Although 2008 guidelines of the European Society of Cardiology (ESC) included the assessment of individual risk of early mortality associated with PE ( 6 - 8 ), prognostic factors in PE patients with Pulmonary Embolism Severity Index (PESI) class I-III had not yet been clearly defined. The 2014 ESC guidelines included the advanced risk stratification of PE patients with PESI I-III ( 9 ), but the clinical implications of prognostic assessment and therapeutic strategy in these patients still warrant further investigation, because mortality in hemodynamically stable patients remains unknown ( 10 - 14 ).…”
mentioning
confidence: 99%
“…Recent data suggest these numbers may be even higher (37). Volschan (19) presents overall mortality 14.1% and as independent death risks emphasizes age > 65 y; bed rest >72 h; chronic cor pulmonale; sinus tachycardia and tachypnoe. We found the overall mortality for PE 17.6 % in our patient set > 65 y with decreasing tendency among elderly people with PE action of LMWH prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Although circulatory collapse occurs in a relatively small proportion of the elderly, these latter patients are much more likely to have sustained massive pulmonary emboli and often have evidence of neurologic defi cits and fi ndings of pulmonary hypertension. Immobilization in medical ward (12,19) is due to illness (e.g. infection, malignancy, heart failure, myocardial infarction, stroke, frailty, geriatric giants etc.).…”
Section: Discussionmentioning
confidence: 99%